2007
DOI: 10.2967/jnmt.106.035972
|View full text |Cite
|
Sign up to set email alerts
|

Blood Volume Analysis: A New Technique and New Clinical Interest Reinvigorate a Classic Study

Abstract: Blood volume studies using the indicator dilution technique and radioactive tracers have been performed in nuclear medicine departments for over 50 y. A nuclear medicine study is the gold standard for blood volume measurement, but the classic dualisotope blood volume study is time-consuming and can be prone to technical errors. Moreover, a lack of normal values and a rubric for interpretation made volume status measurement of limited interest to most clinicians other than some hematologists. A new semiautomate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
42
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 18 publications
0
42
0
3
Order By: Relevance
“…Trends in these variables may allow the early detection of HF decompensation. Transcutaneous thoracic impedance 18 and blood volume analysis 19 can assess instantaneous volume status in chronic HF. These methods can be time-consuming and require a healthcare visit.…”
Section: Discussionmentioning
confidence: 99%
“…Trends in these variables may allow the early detection of HF decompensation. Transcutaneous thoracic impedance 18 and blood volume analysis 19 can assess instantaneous volume status in chronic HF. These methods can be time-consuming and require a healthcare visit.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have identified many areas where measurement of PV and BV would be clinically useful including congestive HF [21, 23-26], sepsis [27], and surgical patients [28]. Research radioisotope measurements, using the indicator dilution technique have traditionally been considered the gold standard for BV and PV assessment [22, 29-32], but they are cumbersome and expensive, especially at the bedside. An FDA-approved BV measurement system (Daxor, BVA-100) has commercialized the RISA technique and utilized comparisons to the ideal BV weight method [33].…”
Section: Discussionmentioning
confidence: 99%
“…A semi-automated blood volume analyzer, the BVA-100, also uses indicator dilution principles to measure plasma volume using radioactive iodinated human serum albumin. Although the BVA-100 system improves accuracy and eliminates the many time-consuming and difficult steps required for on-site standard testing, it is expensive, and is not suitable for repeated measurement of CBV [5,6].…”
mentioning
confidence: 99%
“…The indicator dilution technique using radioactive tracers has been used in nuclear medicine departments for over 50 years to monitor CBV in patients with pheochromocytoma [5]. A semi-automated blood volume analyzer, the BVA-100, also uses indicator dilution principles to measure plasma volume using radioactive iodinated human serum albumin.…”
mentioning
confidence: 99%
See 1 more Smart Citation